The Use of Songs to Improve Thai Language Proficiency of Vietnamese Students - Pornumpaisakul, Nition; mahavarakorn, Supak; Yenbutra, Phagasri; Kiều Yến, Nguyễn; Thị Loan Phúc, Nguyễn (Journal of Information and Learning [JIL], 2022)
The purpose of the study was to construct a Thai language textbook using songs to improve Thai language learning of Vietnamese students. The textbook, which was a research instrument of the study, was constructed by using Thai songs. It consisted of eight units: Unit 1 Chang Chang Chang (Elephant, Elephant, Elephant), Unit 2 O Thale Saen Ngam (What a beautiful Sea!), Unit 3 Ta In Kap Ta Na (Grandpa In and Grandpa Na), Unit 4 Loi Krathong, Unit 5 Wan Duean Pi (Day, Month and Year), Unit 6 Khu Kat (A Rival), Unit 7 Sabai Di Rue Plao (Are You Okay?) and Unit 8 Ya Yom Phae (Don’t Give up!). The research instrument was developed according to the advice of three experts and tried out with 21 Vietnamese participants who were the second-year undergraduate students, majoring in Thai Studies at the University of Foreign Language Studies-The University of Danang. The study showed that the Thai language textbook comprised of songs with lyrics and vocabulary. The additional knowledge and language use also provided with an explanation in Vietnamese language in some parts. The book also offered activities that students could revise the lessons on their own. The study showed that the textbook with song activities improved the students’ language use and language skills, especially listening skills. They could do exercises and achievement tests. The effectiveness of the materials, E1=75.86/E2=74.71, showed that songs could improve the Vietnamese students’ language use and language skills. It can be concluded that the Thai language textbook can be used as a learning material for the Vietnamese students. Moreover, it can be used as a learner-centered material which students can study on their own.